Comparison of Pasteur and Behringwerke antivenoms in envenoming by the carpet viper (Echis carinatus). Issue 6214 (1st March 1980) - Warrell, D A; Warrell, M J; Edgar, W; Prentice, C R; Mathison, J; Mathison, J
Abstract : Bites and envenoming by the carpet viper Echis carinatus are common medical emergencies in parts of Nigeria, but the most effective use of the various commercially produced antivenoms in treatment has not been established. Pasteur Paris Echis monospecific and Behringwerke West and North Africa Bitis-Echis-Naja polyspecific antivenoms were compared in two groups of seven patients with incoagulable blood after E carinatus bites. In both groups spontaneous bleeding stopped within a few hours and local swelling subsided within two weeks after the initial antivenom injection. Pasteur antivenom (20-40 ml) restored blood coagulability within 12 hours in all cases, but 60--180 ml of Behringwerke antivenom was effective in only four cases. Persisting venom procoagulant activity was observed in the remaining three cases. Despite its potency in the mouse protection test, Behringwerke antivenom is unreliable and unpredictable in neutralising venom procoagulant in humans bitten by E carinatus.